Clinical vitamin D levels are associated with insular volume and inferior temporal gyrus white matter surface area in community-dwelling individuals with knee pain - Strath, Larissa J.; Hernandez, Pedro Valdes; Nodarse, Chavier Laffitte; Johnson, Alisa J.; Edberg, Jeffrey D.; Fillingim, Roger B.; Cruz-Almeida, Yenisel (Frontiers in Neuroscience, 2022)
Context: Vitamin D is an essential, fat soluble micronutrient long-known for its effects on calcium homeostasis and bone health. With advances in technology, it is being discovered that Vitamin D exerts its effects beyond the musculoskeletal system. Vitamin D has since been noted in nervous system health and functioning, and is becoming a target of interest in brain health, aging, and chronic pain outcomes. Objectives: We and others have previously shown that deficient Vitamin D status is associated with greater pain severity across a variety of conditions, however the reason as to why this relationship exists is still being understood. Here, we sought to examine associations between Vitamin D status and brain structure in those with chronic knee pain. Methods: Whole brain analyses and imaging techniques were employed and serum Vitamin D were collected. Results: We discovered that individuals who were either clinically deficient (<20 ng/mL) or insufficient (20-30 ng/mL) in serum Vitamin D had significant differences in the grey matter of the insular cortex, inferior temporal gyrus, middle temporal gyrus, as well as decreased white matter surface area in the inferior temporal sulcus compared to those considered to have optimal levels (>30 ng/mL) of serum Vitamin D. Conclusions: These data suggest that Vitamin D, or lack thereof, may be influencing pain outcomes by mediating changes in regions of the brain known to process and interpret pain. More research understanding this phenomenon as well as the effects of Vitamin D supplementation is warranted.